2012
DOI: 10.1002/pip.1250
|View full text |Cite
|
Sign up to set email alerts
|

Absorption coefficient for the intraband transitions in quantum dot materials

Abstract: In this paper, we present calculations of the absorption coefficient for transitions between the bound states of quantum dots grown within a semiconductor and the extended states of the conduction band. For completeness, transitions among bound states are also presented. In the separation of variables, single band k-p model is used in which most elements may be expressed analytically. The analytical formulae are collected in the appendix of this paper. It is concluded that the transitions are strong enough to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…An analogous study was made in [14] of the transitions between the confined and extended CB states. It was found that, although the overlap between confined and extended states is small, the high density of extended states leads to a significant absorption coefficient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An analogous study was made in [14] of the transitions between the confined and extended CB states. It was found that, although the overlap between confined and extended states is small, the high density of extended states leads to a significant absorption coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…We can define the polarization by the Euler angles (<f>,&) characterizing its direction. Thus (14) and the same for its components. We use the following nomenclature,…”
Section: E {W V (T)\w V (T)) = En/« = Ekkmentioning
confidence: 97%
See 2 more Smart Citations
“…[ 4,5 ] In order to better understand the problems facing existing QD-IBSCs, there have been several recent theoretical studies into the absorption of subbandgap photons by the QDs. Optical matrix elements have been calculated for intraband (IB ↔ CB) [ 9,10 ] and interband (VB ↔ IB) [ 11,12 ] transitions using, in the former case, a one-band k·p method, and, in the latter case, the so-called empirical k·p Hamiltonian (EKPH) method, [ 11 ] which is a four-band k·p method.…”
Section: Introductionmentioning
confidence: 99%